Copper Based Alloys Hardenable by Precipitation - Irina Carceanu; Adrian Gavril Bolojan; George Surdu; Catalin Fratila; Alexandru Savastre (Chemical Engineering Transactions, 2021)
The paper presents the experimental research conducted with the purpose of accomplishing long products out of special copper-based alloys, from Cu-Cr-Zr systems, hardenable by precipitation, appropriate for large domains of utilization within top industries realized by modern casting – deforming procedures. Therefore, one of the modern technologic alternatives meeting these requirements is horizontal continuous casting which ensures the realization of long semi-fabricated materials out of special alloys that can be used in cast state and/or plastically deformed, in warmth and/or cold, for the accomplishment of certain products required on the market. The effect of precipitation function of hardening degree applied to the samples put in solution is quantified on consecrated compositions of the Cu-Cr-Zr alloys, containing ˜ 1% Cr and ˜ 0.12% Zr respectively, after the solubility treatment. The macroscopic resistance determinations as well as the electronic microscope and X-ray investigations shall furthermore lead to the accomplishment of a concluding image on the mechanism of precipitation within the analysed systems. Key words: Copper based alloys, horizontal continuous casting.